Porcine spleen as a model organ for blunt injury impact tests: An experimental and histological study - Kochová, Petra; Malečková, Anna; Pálek, Richard; Liška, Václav; Bońkowski, Tomasz; Horák, Miroslav; Grajciarová, Martina; Tonar, Zbyněk (Anatomia, histologia, embryologia, 2022)
The spleen is a large and highly vascularized secondary lymphatic organ. Spleen injuries are among the most frequent trauma-related injuries in the abdominal region. The aims of the study were to assess the volume fractions of the main splenic tissue components (red pulp, white pulp, trabeculae and reticular fibres) and to determine the severity of splenic injury due to the experimental impact test. Porcine spleens (n = 17) were compressed by 6.22 kg wooden plate using a drop tower technique from three impact heights (50, 100 and 150 mm corresponding to velocities 0.79, 1.24 and 1.58 m/s). The pressure was measured via catheters placed in the splenic vein. The impact velocity was measured using lasers. The severity of induced injuries was analysed on the macroscopic level. The volume fractions of splenic components were assessed microscopically using stereology. The volume fraction of the red pulp was 76.4%, white pulp 21.3% and trabeculae 2.7% respectively. All impact tests, even with the low impact velocities, led to injuries that occurred mostly in the dorsal extremity of the spleen, and were accompanied by bleeding, capsule rupture and parenchyma crushing. Higher impact height (impact velocity and impact energy) caused more severe injury. Porcine spleen had the same volume fraction of tissue components as human spleen, therefore we concluded that the porcine spleen was a suitable organ model for mechanical experiments. Based on our observations, regions around hilum and the diaphragmatic surface of the dorsal extremity, that contained fissures and notches, were the most prone to injury and required considerable attention during splenic examination after injury. The primary mechanical data are now available for the researchers focused on the splenic trauma modelling.
Keywords: nemoci prasat; Swine; porcine spleen; prasata; mechanical behaviour; zvířata; Humans; Wounds, Nonpenetrating; quantitative microscopy; impact loading; Spleen; Swine Diseases; tupá poranění; lidé; slezina; Animals